O ensino de arte contemporânea: uma proposta de formação continuada para professores de Arte dos anos finais do Ensino Fundamental - DINIZ, Maria de Jesus dos Santos (2021)
This research verified how the different visual languages of contemporary art contribute to the expansion of the conception of Art in teachers of the Elementary School - Final Years of São Luís-MA. To achieve this goal, the study offered the Contemporary Art Training Course for Art teachers working in the municipal education system of São Luís in an online format, created within the Nutror tool and divided into five modules composed of theoretical and practical activities in the format of videos and educational material. Twelve teachers participated in this study, being five masters and seven specialists. As for the focus, we opted for the characteristics of the qualitative research approach, following the framework of this investigation, the selected method of procedure was the cartographic research. The instruments for data collection were structured initial and final interviews, documentary research, teachers' reports, focus groups, and audiovisual recordings. To collect the data, digital platforms were used on line through Google tools such as Google Forms and Google Meet, the first for the questionnaire, expression of interest and registration; the second, audio and video for the interviews and focus groups. The analysis and interpretation of the data generated, with a qualitative focus, was carried out using charts, tables and graphs to systematize the statements of the participants during the interviews (initial and final) in categories and subcategories, and also calculated the frequency of citation of each of them. These data showed that most of the participating teachers had a significant lack of contact with contemporary art during their initial training. However, the data collected and analyzed in the post-intervention period show that the proposed continuing education course contributed for the participants to acquire and expand their knowledge about contemporary art. In this research, we resorted mainly to the studies of Archer (2012), Heinichi (2014), Smith (2010), Danto (1997), Cocchiarale (2006), Canton (2009, 2013), Chiarelli (1995), Cantanhede (2008, 2012), Pacheco (2005), Silva (2015), Macedo (2017), Ferraz and Fusari (2009), Richter (2003), Subtil (2012), Vieira (2013), Silva (2019), Barbosa (1989, 2002, 2012), Oliveira (2016), Imbernón (2013), Pimenta (1997), Bardin (1979), Deleuze e Guattari (1995), Lakatos e Marconi (1991), among others. The official documents that govern Brazilian basic education and initial and continued teacher training were also analyzed: Law of Directives and Basis of National Education of n°9393/96, National Curricular Guidelines for Basic Education (2014), National Curricular Parameters - Art (1998), the Common National Curricular Base (2017), Curricular Document of the Maranhense Territory (2019), Curricular Proposal of the Municipal Public Teaching Network of São Luís (2020, provisional document), National Curricular Guidelines for Initial and Continuing Training for Training (2015) and Continuing Training Policy through the Municipal Secretariat of Education (2020, preliminary).